Q: What are the cowardinates for y 4x-3?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

It depends on what y is equal to. Insert what y is into the equation: y+4*3=? But simplified, it's... y+12=?

4x3=12 250-12=238 238/50=4.76

4x3+10x2+2x+5= (2x+5)(2x2+1)

Mathematics. An algebraic expression consisting of only one term is called a monomial therefore:4x3 is a monomial it has only have one term.

If the degree of the polynomial is odd, the range is all real numbers - for example, y = x5. If the degree is even, use derivatives to find maxima or minima. You learn about derivatives, maxima and minima in any basic calculus course. Example: y = x4 - 3x3 Take the derivative: y' = 4x3 - 9x2 Solve for zero: 4x3 - 9x2 = 0 This will give you two maxima or minima; in this case, check at which of these points the function has the smallest value. Because of the positive coefficient of the leading term, the function values go from this point all the way to plus infinity.

Related questions

It depends on what y is equal to. Insert what y is into the equation: y+4*3=? But simplified, it's... y+12=?

4x3 times 4x3 = 16x6

21-4x3 is equal to 9.

(4x3)+2 = 14

Yes, 4x3 or 3x4 does equal 12.

Interpreting this equation as y=4x3+4x2 This is not a quadratic equation. By definition, a quadratic equation is a polynomial equation of order two, meaning it is composed only of coefficients multiplied by x's raised to any exponential power of maximum 2. The most that any of the exponents in the equation can be is 2. Since this equation has a term of 4x3, it is not quadratic since this term has an exponent of 3. This means that the equation is of degree three. This equation is a cubic equation.

When x = 2, 4x3 = 32

gcf of 4x3=6 gcf of 3x8=8

4x3+12x2+3x+9

4x3=12 250-12=238 238/50=4.76

One step you usually want to take is to move any perfect square out of the radical. Example 1, with numbers: root(12) = root(4x3) = root(4) x root(3) = 2 root(3) Example 2, with variables: root(y cubed) = root(y squared times y) = root(y squared) times root(y) = y root(y)

12x